Penerapan Metode Demonstrasi Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Di Kelas IV Sekolah Dasar 020 Rambah Hilir Tahun Pelajaran 2016/2017 - Nurmida Sijabat (STKIP Rokania Pasir Pangaraian, 2018)
This research is action research. The focus of this research is learning by using demonstration methods to improve student learning outcomes in Indonesian language subjects in grade IV elementary school. The research instruments are syllabus, learning implementation plan (RPP) of student worksheet (LKS), lattice and questionnaire, ie test sheet and student observation sheet. Result of research that student's absorption before before improvement / prasiklus average 64.09, in cycle 1 increased mean 71.81 and in cycle II become more increase average 76.81. Thus the implementation of demonstration methods to improve student learning outcomes in Indonesian subjects in grade IV Primary School